Analisis Rendemen dan Skrining Senyawa Metabolit Sekunder Ekstrak Metanol Daun Violces (Viola odorata) - Sandi Al Afif Fathoroni Putra; Surahmaida Surahmaida (Yayasan Literasi Sains Indonesia, 2023)
Violces (Viola odorata) is an herbal plant from the Violaceae family and is used in traditional medicine. This is believed to be due to the presence of phytochemical compounds in the Violces plant that provide the pharmacological activity. This study aims to determine the extract yield value and chemical compound groups contained in Violces leaves. The research method consists of four stages, namely extraction, evaporation, yield value calculation, and phytochemical screening. Violces leaf extract was obtained by maceration for 3 days using methanol as the solvent, then filtered and concentrated using a rotary evaporator. The concentrated extract of Violces leaves was then used to calculate the yield value and subjected to phytochemical screening for alkaloids, flavonoids, tannins, saponins, steroids and terpenoids. The method used for the identification of secondary metabolite compounds involve the use of chemical reagents, indicated by color changes, precipitate formation, foam/bubbles, and rings. The results of the study showed a methanol extract yield of Violces leaves of 26,70%. The phytochemical screening test of the methanol extract of Violces leaves revealed the presence of tannins, saponins and steroids.